Math, asked by sanjaysankarlal1978, 2 months ago

(√2+√5−√2)−(√2+√5−√9)=1​

Answers

Answered by kanchankumari0201198
1

Answer:

(√2+√5−√2)−(√2+√5−√9)=1

will u please help me need some brainliest

Step-by-step explanation:

Answered by alina8332
0
S=(1+5
2

x)
9
+(1−5
2

x)
9

Let k=5
2


Then the above binomial expansion changes to
S=(1+k)
9
+(1−k)
9


=[1+
9
C
1

k+
9
C
2

k
2
+...
9
C
9

k
9
]+[1−
9
C
1

k+
9
C
2

k
2

9
C
3

k
3
...−
9
C
9

k
9
]

=2[1+
9
C
2

k
2
+
9
C
4

k
4
+
9
C
6

k
6
+
9
C
8

k
8
]
Hence in total 5 terms will be there.
Similar questions